2008
DOI: 10.1016/j.jrp.2008.06.009
|View full text |Cite
|
Sign up to set email alerts
|

On feeling understood and feeling well: The role of interdependence

Abstract: The present research examined whether people feel happier and healthier when they feel more understood in daily social interactions. A two-week diary study showed that people reported greater life satisfaction and fewer physical symptoms on days in which they felt more understood by others. Moreover, we found that individuals who tend to see themselves in relations to others (i.e., women or those scored high on interdependent self-construal measure) showed a stronger association between daily felt understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 17 publications
8
91
0
1
Order By: Relevance
“…Kimura and Katayama's (2013) electrophysiological study results support the notion that risk-aversive-related outcome evaluation is associated with using the majority rule in a manner consistent with the present findings. On the other hand, previous studies have focused on whether self-construal as an individual difference construct plays a vital role in, for example, potential biases resulting from judgmental heuristics (e.g., Bry, Follenfant, & Meyer, 2008;Cheek & Norem, 2017) and in mediating social emotions (e.g., Hui, Fok, & Bond, 2009;Levinson, Langer, & Rodebaugh, 2011;Lun, Kesebir, & Oishi, 2008) and consumer behaviors (e.g., Chen, 2009;Wang & Keh, 2017). The present study extends previous work on the role of self-construal in the scope of individual decision making.…”
Section: Discussionsupporting
confidence: 71%
“…Kimura and Katayama's (2013) electrophysiological study results support the notion that risk-aversive-related outcome evaluation is associated with using the majority rule in a manner consistent with the present findings. On the other hand, previous studies have focused on whether self-construal as an individual difference construct plays a vital role in, for example, potential biases resulting from judgmental heuristics (e.g., Bry, Follenfant, & Meyer, 2008;Cheek & Norem, 2017) and in mediating social emotions (e.g., Hui, Fok, & Bond, 2009;Levinson, Langer, & Rodebaugh, 2011;Lun, Kesebir, & Oishi, 2008) and consumer behaviors (e.g., Chen, 2009;Wang & Keh, 2017). The present study extends previous work on the role of self-construal in the scope of individual decision making.…”
Section: Discussionsupporting
confidence: 71%
“…In this sense, we have identified that felt understanding and misunderstanding have a causal influence on a subtle sense of efficacy by changing the visual and geographical world that we face every day. Combined with an earlier finding that people experience fewer physical symptoms when they feel understood by others (Lun, Kesebir, & Oishi, 2008), then felt understanding appears to nurture a sense of efficacy and make people physically stronger (in the sense that they can tolerate pain more and perceive the world as more approachable). In contrast, felt misunderstanding appears to generate a sense of ineptitude and make people physically weaker.…”
Section: Discussionmentioning
confidence: 83%
“…Lun, Oishi, Coan, Akimoto, & Miao, 2010). Finally, it is important in the future to examine whether the previously reported link between felt understanding and physical health (Lun et al, 2008) is mediated by pain tolerance and slant and distance perceptions.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it facilitates psychological and physical well-being in one’s daily social interactions (Lun, Kesebir, & Oishi, 2008; Oishi et al, 2010). For example, over the course of a 2-week diary study, White and Asian Americans reported greater life satisfaction and fewer daily physical health problems (e.g., headaches, stomachaches) on days when they felt more understood by others during social interactions (Lun et al, 2008). Furthermore, feeling understood by one’s interaction partner carries over to influence physical health the next day; White and Asian Americans who felt more understood on 1 day reported fewer physical health problems the following day (Lun et al, 2008).…”
Section: Felt Understanding and Well-beingmentioning
confidence: 99%
“…For example, over the course of a 2-week diary study, White and Asian Americans reported greater life satisfaction and fewer daily physical health problems (e.g., headaches, stomachaches) on days when they felt more understood by others during social interactions (Lun et al, 2008). Furthermore, feeling understood by one’s interaction partner carries over to influence physical health the next day; White and Asian Americans who felt more understood on 1 day reported fewer physical health problems the following day (Lun et al, 2008). Similarly, when White and African Americans felt that their personal self was understood by partners during daily social interactions, they also felt happy and pleasant during the interaction (Oishi, Koo, & Akimoto, 2008).…”
Section: Felt Understanding and Well-beingmentioning
confidence: 99%